Predictive value of skill performance in terms of physical indicators in 14-year-old football players - Mahmood Abd Al Jaleel Abd Al Zahra; Ali Kadhim Hadi; Ahmed Khattar Saad (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.